Sosialisasi Terhadap Upaya Penegakan Hukum Pungutan Liar (Pungli) Di Desa Kenangan Baru - Gerald Elisa Munthe (CV. Multi Kreasi Media, 2024)
Bandar Khalipah Hamlet XI Village, Percut Sei Tuan Subdistrict, is a village whose citizens in their daily lives are familiar with information and communication technology. The people of Bandar Khalipah Dusun XI Village need to understand what is meant by illegal levies (pungli) committed by a person, government official, or official. The implementation method is carried out by lectures and discussions with the community accompanied by questions and answers. The results show that law enforcement efforts through a humanism approach are a movement to raise awareness of human values owned by the community with the aim of creating qualified legal awareness and avoiding legal loopholes by means of heart to mind, communication approach (dialogue), mediation, friendship approach and family approach that has been by the Village Government together with local community leaders so as to get clear output and avoid legal problems.